Niclosamide—A promising treatment for COVID‐19. (11th April 2022) - Singh, Shivani; Weiss, Anne; Goodman, James; Fisk, Marie; Kulkarni, Spoorthy; Lu, Ing; Gray, Joanna; Smith, Rona; Sommer, Morten; Cheriyan, Joseph
Abstract : Vaccines have reduced the transmission and severity of COVID‐19, but there remains a paucity of efficacious treatment for drug‐resistant strains and more susceptible individuals, particularly those who mount a suboptimal vaccine response, either due to underlying health conditions or concomitant therapies. Repurposing existing drugs is a timely, safe and scientifically robust method for treating pandemics, such as COVID‐19. Here, we review the pharmacology and scientific rationale for repurposing niclosamide, an anti‐helminth already in human use as a treatment for COVID‐19. In addition, its potent antiviral activity, niclosamide has shown pleiotropic anti‐inflammatory, antibacterial, bronchodilatory and anticancer effects in numerous preclinical and early clinical studies. The advantages and rationale for nebulized and intranasal formulations of niclosamide, which target the site of the primary infection in COVID‐19, are reviewed. Finally, we give an overview of ongoing clinical trials investigating niclosamide as a promising candidate against SARS‐CoV‐2.